Mapping the landscape and research trend of imaging diagnosis in lymphoma: a bibliometric analysis from 1976 to 2024 - Ma, Yi (Frontiers in Medicine, 2025)
BackgroundOver the past five decades, extensive research has been conducted on lymphoma imaging diagnostics; however, no bibliometric analysis has been performed in this area. Therefore, we undertook a bibliometric analysis to clarify the progress and current state of research in this field.MethodsWe conducted a search of the Web of Science Core Collection database for articles related to imaging diagnosis and lymphoma, focusing exclusively on English-language publications up to June 20, 2024. We analyzed and visualized various aspects, including publication trends, journals, co-authorship networks, countries, institutions, and keywords. To examine research trends in this field, we utilized bibliometric analysis tools such as VOSviewer, CiteSpace, and R4.3.3.ResultsFrom 1976 to 2024, a total of 10,410 publications were produced on this topic, with 2021 marking the peak in publication numbers. The most significant contributions in this research area were found in the fields of Radiology, Nuclear Medicine & Medical Imaging, Oncology, and Hematology. The United States, China, and Japan were the leading contributors. Zucca Emanuele ranked first among authors, followed closely by Meignan Michel. In terms of institutions, Assistance Publique Hôpitaux de Paris was the most prominent. The most frequently used keywords included positron emission tomography, computed tomography, and non-Hodgkin’s lymphoma.ConclusionThis study presented a bibliometric analysis of lymphoma imaging diagnosis, highlight showcasing research trends, influential significant studies, and collaborative networks. The analysis identified key contributions to the field and provide insights for future research directions.